Montana territory [large type] - West, Charles (West, Charles. John Hawk western, 2021)
Raised among the Blackfoot, John Hawk is a valuable asset to the US Army. As a military scout at Fort Ellis, he is able to cross the line between two worlds'and help keep the peace. But when he disobeys a direct order from his commander, Hawk is immediately dismissed from his post. That was the army's first mistake. The second was losing track of a small mule train en route to Helena. At the request of his former lieutenant, Hawk leaves his cabin on the Boulder River to help find the missing party. The mule train, it appears, was ambushed by a savage gang of outlaws. Most of the travelers were murdered. Only a few survived to tell the tale. And now it's up to Hawk to stalk the killers across the lawless Montana territory--alone. No backup. No calvary. No mercy ...